Research into effect of electrochemical etching conditions on the morphology of porous gallium arsenide - Vambol, Sergij; Bogdanov, Ihor; Vambol, Viola; Suchikova, Yana; Lopatina, Hanna; Tsybuliak, Natalia (Eastern-European Journal of Enterprise Technologies, 2017)
The method for the formation of porous gallium arsenide in a solution of hydrochloric acid was improved. The goal of present research was to establish correlation between conditions of electrochemical etching of gallium arsenide crystals and morphology of low-dimensional structures. Porous layers were formed by the method of electrochemical etching in a solution of hydrochloric acid. The mode of electrolyte agitation was applied. This makes it possible to avoid the formation of bubbles on the surface of the crystal during etching and leads to the formation of regular porous space. Basic regularities in the formation of porous spaces were studied. It was shown that morphological properties of por-GaAs depend on etching conditions. The effect was explored of current density on the thickness of a porous layer and diameter of pores. It was established that the composition and concentration of electrolyte correlate with surface porosity and affect the rate of crystal dissolution reaction. Etching time determines thickness of a porous layer and surface porosity. Chemical composition of por-GaAs was explored. An oxide layer was not formed on the surface of the examined samples; oxygen was present only in small concentrations. Stoichiometry of the samples was disrupted towards an excess of gallium atoms